Productive Waqf Management Model Innovation for Community Economic Empowerment in the Digital Era - Aristyanto, Erwan; Riduwan, Riduwan (Badan Wakaf Indonesia, 2025)
Waqf is an economic instrument that has great potential in empowering society, especially in countries with large Muslim populations. In this digital era, innovation in productive waqf management can be a solution to increase effectiveness and efficiency in managing waqf funds. This research aims to explore innovative productive waqf management models and their impact on community economic empowerment. Through a comprehensive literature review and analysis of various journal articles, books and other relevant sources, this research examines digital waqf innovation practices in developing countries. These findings highlight the potential of digital waqf innovations, such as crowdfunding, blockchain technology, and mobile applications, to increase the efficiency, accountability and reach of waqf management. This technology can expand the collection of waqf funds, increase transparency, and However, challenges such as the need to increase digital literacy, public trust in digital waqf management, and align waqf regulations with advances in digital technology must be addressed. This study provides insights and recommendations for stakeholders in developing countries, especially Indonesia, to utilize digital waqf innovation to support sustainable development programs more optimally. facilitate public access to participate in waqf.